Kepemimpinan Transformasional, Motivasi Dan Disiplin Kerja dan Pengaruhnya Terhadap Kinerja (Studi pada Pegawai Di Kantor Kecamatan Ngunut Kabupaten Tulungagung) - Widya Citraningtyas (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This research aims to: analyse the influence of Transformational Leadership among variables on performance clerk; Analyse the influence of motivational variables on performance among employees; Analyse the influence of the working Discipline among variables on performance clerk; Analyzing simultaneously the significant influence of transformational leadership, motivation and discipline work against employee performance; analyse the influence of the most dominant Transformational Leadership among variables, motivation and discipline work against the performance of employees. This research uses Descriptive Quantitative. the population in this research is Ngunut Subdistrict Office clerk Tulungagung district. The researcher does not specify a sample, because all members of the population will be examined. The technique is a method of data collection now. In this study, researchers used the software (software), Microsoft Office Excel 2007 to carry out a descriptive and statistical analysis software (software) Statistical Package for Social Sciences (SPSS) for Windows version 21.0 to carry out the test, test the classical, hypothesis testing and multiple linear regression analysis, , The results showed that there were simultaneous or partially significant effects between Transformational Leadership variable, motivation and discipline work against the performance of employees: as for the most dominant influence i.e. variable Discipline work.